2019
DOI: 10.1158/1541-7786.mcr-18-1191
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Induces Metabolic Reprogramming of the Tumor Stroma in Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is comprised of metabolically linked distinct compartments. Cancer-associated fibroblasts (CAF) and nonproliferative carcinoma cells display a glycolytic metabolism, while proliferative carcinoma cells rely on mitochondrial oxidative metabolism fueled by the catabolites provided by the adjacent CAFs. Metabolic coupling between these reprogrammed compartments contributes to HNSCC aggressiveness. In this study, we examined the effects of cigarette smoke–exposed CAFs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…This is exemplified by the different expression patterns seen in different methods of CAF identification (44). As recent research has shown, CAF function can be altered by environmental factors (19). Many believe that CAFs, like tumor-associated macrophages, may have either pro-tumoral or anti-tumoral effects depending on subtype or activation (78).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is exemplified by the different expression patterns seen in different methods of CAF identification (44). As recent research has shown, CAF function can be altered by environmental factors (19). Many believe that CAFs, like tumor-associated macrophages, may have either pro-tumoral or anti-tumoral effects depending on subtype or activation (78).…”
Section: Discussionmentioning
confidence: 99%
“…CAFs modulate the TME via the secretion of autocrine and paracrine cytokines, as well as extracellular matrix components that provide scaffolds to support the growing tumor cell nests. Many of the classic "hallmarks of malignancy", as well as emerging hallmarks such as immune evasion and metabolic compartmentalization, are influenced by the presence and functional states of CAFs (6,(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In HNSCC, autophagy is induced by various risk factors. Major risk factors such as tobacco and alcohol have been found to induce oxidative stress, leading to chronic inflammation and induction of enhanced level of autophagy and finally resulting in oncogenic mutations 14 . HPV, an emerging risk factor for HNSCC, might also induce autophagy by enhancing expression of ARGs 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence demonstrates the cigarette smoke-induced metabolic reprogramming of cancer-associated fibroblasts (CAFs) towards a highly glycolytic phenotype. The highly glycolytic phenotype induces metabolic coupling and enhances the aggressiveness in HNSCCs, implicating oxidative stress in not only altering squamous metabolism but also shifting tumor stroma into a pro-oncogenic metabolic environment [ 104 ]. Additionally, CAFs may facilitate the glycolytic switch of HNSCCs by secreting HGF, which in turn induces bFGF secretion from HNSCCs to promote fibroblast proliferation [ 105 ].…”
Section: Metabolic Dependencies In Squamous Cell Carcinomasmentioning
confidence: 99%